Suppressing spectator-induced dephasing through optimized dynamical decoupling implementation - Hayoung Jeong; Youngdu Kim; Beomgyu Choi; Minkyun Cho; Seungwook Woo; Yonuk Chong; Yong-Ho Lee; Hwan-Seop Yeo (Scientific Reports)
Abstract Dynamical decoupling (DD) is a well-established technique for protecting quantum systems from environmental noise. DD effectively mitigates decoherence in superconducting quantum computing systems, where precise implementation plays a crucial role in optimizing its performance. This study investigates how DD implementation timing and sequence design critically affect spectator-induced dephasing from adjacent qubits. We find that excited states of adjacent qubits dramatically degrade operational qubit coherence. We demonstrate that DD sequences applied to adjacent qubits effectively suppress this dephasing. This protection persists even when adjacent qubits remain in superposition states during the sequence. Through systematic characterization of Carr-Purcell-Meiboom-Gill (CPMG) sequences, we show that implementation timing strongly impacts protection effectiveness. While optimal timing achieves substantial coherence enhancement, improper sequence delays can severely degrade protection. Our results highlight the importance of precise timing control for implementing DD in optimizing multi-qubit quantum circuits.